Optimisation of water, temperature and voltage management on a regenerative fuel cell - Van Tonder, Petrus Jacobus Malan (My University, 2012)
“Never before in peacetime have we faced such serious and widespread shortage of energy” according to John Emerson, an economist and power expert for Chase Manhattan Bank. Many analysts believe that the problem will be temporary, but others believe the energy gap will limit economic growth for years to come. A possible solution to this problem can be fuel cell technology. Fuel cells (FCs) are energy conversion devices that generate electricity from a fuel like hydrogen. The FC however, could also be used in the reverse or regenerative mode to produce hydrogen. The reversible fuel cell (RFC) can produce hydrogen and oxygen by introducing water to the anode electrode chamber, and applying a potential across the anode and cathode. This will cause the decomposition of the water to produce oxygen at the anode side and hydrogen at the cathode side. In order to make this process as efficient as possible several aspects need to be optimised, for example, the operation temperature of the RFC, water management inside the RFC and supply voltage to the RFC. A three cell RFC and its components were constructed. The three cell RFC was chosen owing to technical reasons. The design factors that were taken into consideration were the different types of membranes, electrocatalysts, bipolar plates and flow topologies. A water trap was also designed and constructed to eliminate the water from the hydrogen water mixture due to water crossover within the MEA. In order to optimise the operation of the RFC a number of experiments were done on the RFC. These experiments included the optimal operating voltage, the effect that the temperature has on the production rate of hydrogen, and the effect that the water flow through the RFC has on the production rate of hydrogen. It was found that there is no need to control the water flow through the RFC because it had no effect on the production rate of hydrogen. The results also showed that if the operating temperature of the RFC were increased, the energy it consumes to warm the RFC significantly decreases the efficiency of the whole system. Thus the RFC need not be heated because it consumes significantly more energy to heat the RFC compared to the energy available from the hydrogen produced for later use. The optimised operating voltage for the three cell RFC was found to be 5.05 V. If the voltage were to be increased or decreased the RFC efficiency would decrease.
Thesis (M. Tech. - (Engineering: Electrical, Department: Electronic Engineering, Faculty of Engineering and Technology)) -- Vaal University of Technology, 2011.
Keywords: Fuel cells; Regenerative fuel cells; Energy conversion devices; Reversible fuel cell; Water -- Anode electrode chamber; 621.312429; Fuel cells; Hydrogen as fuel.